1977
DOI: 10.1002/sapm1977563267
|View full text |Cite
|
Sign up to set email alerts
|

Rook Theory—IV. Orthogonal Sequences of Rook Polynomials

Abstract: We explain combinatorially the occurrence of certain classical sequences of orthogonal polynomials as sequences of rook polynomials, and we give some new examples related to general stairstep boards.is defined to be the vector r (B)=(rt,rf,rf, ... ), where rt = 1. Note that for sufficiently large i, r/ = O. Two boards are rook equivalent if they have the same

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 5 publications
(5 reference statements)
1
8
0
Order By: Relevance
“…Goldman et al [14] then introduced a new version of the rook polynomial of a Ferrers board and gave it a combinatorial interpretation, which showed that it had all integer roots. Subsequent work with Ferrers boards and this rook polynomial have led to models for binomial type theorems [17] and to connections with chromatic polynomials [15], orthogonal polynomials [12,16], hypergeometric series [19], q-analogues and permutation statistics [9,11,20], statistical problems in probability [6], algebraic geometry [7], and digraph polynomials [3,5]. Today there is a very large literature about Ferrers boards.…”
Section: Introductionmentioning
confidence: 97%
“…Goldman et al [14] then introduced a new version of the rook polynomial of a Ferrers board and gave it a combinatorial interpretation, which showed that it had all integer roots. Subsequent work with Ferrers boards and this rook polynomial have led to models for binomial type theorems [17] and to connections with chromatic polynomials [15], orthogonal polynomials [12,16], hypergeometric series [19], q-analogues and permutation statistics [9,11,20], statistical problems in probability [6], algebraic geometry [7], and digraph polynomials [3,5]. Today there is a very large literature about Ferrers boards.…”
Section: Introductionmentioning
confidence: 97%
“…Since the introduction of rook theory by Kaplansky and Riordan [12], the theory has thrived and developed further by revealing connections to, for instance, orthogonal polynomials [7,9], hypergeometric series [10], q-analogues and permutation statistics [2,5], algebraic geometry [3,4], and many more. Within rook theory itself, various models have been introduced, including a p, q-analogue of rook numbers [1,14,20], the j-attacking model [14], the matching model [11], the augmented rook model [13] which includes all other models as special cases, etc.…”
Section: Introductionmentioning
confidence: 99%
“…163-237]. For some recent work on rook polynomials, see Goldman, Joichi, and White [10][11][12][13][14] and Joni and Rota [18]. Let B be a subset of [n] × [n], where [n] = {1, 2, .…”
Section: Rook Polynomialsmentioning
confidence: 99%